Correlation of Vitamin E, Uric Acid and Diet Composition with Histologic Features of Pediatric Nonalcoholic Fatty Liver Disease - Vos, Miriam B. (2012)
OBJECTIVES: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children in the United States. Although changes in diet are often recommended to improve NAFLD, little is known regarding diet influence on histologic features of the disease. METHODS: This was a prospective, cross-sectional registry based study. Children (n=149) enrolled in the multi-center NASH Clinical Research Network had demographic, anthropometric, clinical, laboratory and histology data obtained, including the Block Brief Food Questionnaire. Subjects were grouped by presence or absence of steatohepatitis and grades of histologic features according to NASH-CRN criteria. RESULTS: No significant differences were found between children with steatosis compared to steatohepatitis for fraction of calories from fat, carbohydrates, and protein. Sugar sweetened beverage consumption was low and did not correlate with histologic features, although uric acid, a surrogate marker for fructose intake, was significantly increased in those with definite NASH (p=.008). For all groups, vitamin E consumption was insufficient compared to the recommended daily allowance. Median consumption of vitamin E was lower in children with higher grade of steatosis (8.4 vs 6.1 vs 6.9 for grade I, II and III respectively, p = .05). Those consuming less vitamin C had increased ballooning degeneration (p = 0.05). CONCLUSIONS: Children with NAFLD have a diet that is insufficient in vitamin E and this may contribute to the pathophysiology of NAFLD. In children with NAFLD, reported sugar sweetened beverage consumption is low; however uric acid, which may reflect total fructose consumption, was significantly associated with NASH and should be further evaluated.